Genética populacional de felinos e as ameaças para Puma concolor: estruturação populacional recente e atropelamentos - Saranholi, Bruno Henrique (Universidade Federal de São Carlos, 2018)
Species around the world are increasingly exposed to new threats due to human activities. The main threat is the landscape modification by human activities, resulting in demographic and genetic pattern changes of species populations. Habitat loss and fragmentation may promote the reduction of population size and thus can result in changes in species community. In addition, the modification of landscape can act as a barrier to the individuals movement, limiting gene flow and the population viability. In addition, the needs of searching for new areas to the establishment of territories, may expose individuals to new threats, such as road killing, which is currently considered an important threat to species. In this scenario, some groups are even more sensitive, for example carnivores, which already occur naturally in low densities and require large home ranges. In this sense, this work had as main objectives to evaluate the demographic aspects (minimum population size, abundance and density) of the feline community in four study areas in São Paulo state (Estação Ecológica dos Caetetus, Fazenda Rio Claro da Duratex, Floresta Nacional de Capão Bonito e Parque Estadual Carlos Botelho) using non-invasive sampling and molecular technics. In addition, considering P. concolor as a model, we verified the distribution of its genetic diversity and the occurrence of population structuring in a fragmented landscape within São Paulo and Minas Gerais states. We also evaluated the impact of the loss of individuals due to road killing for the population viability of Puma concolor. The results show an influence of the characteristics of the areas for the occurrence of feline species directly related to their characteristics and requirements. In addition, the results indicate that the loss and fragmentation of the habitat already may represent an important factor for the dispersion of individuals of P. concolor, resulting in the structuring of their populations. This species also suffers the impact of road killing on the loss of individuals which, in long term, also may represent a loss of genetic diversity in their populations. In this way, this work demonstrates, under different aspects, the demographic and genetic impacts on feline species in an increasingly modified environment.
Keywords: Carnívoros; Dispersão; Genética da conservação; Viabilidade populacional; Microssatélites; Carnivorous; Dispersion; Conservation genetics; Population viability; Microsatellites; CIENCIAS BIOLOGICAS::GENETICA